'Cabin pressure': designing affective atmospheres in airline travel. Issue 2 (27th January 2015) - Lin, Weiqiang
Abstract : This article considers the affective design and atmospheric manipulation of spaces of transportation before they are made available for use or consumption. Recent scholarship emphasises the experiential aspect of these onboard spaces, and how affective atmospheres are spontaneously conjured and felt amidst mobility. This article aims to develop a keener understanding of the role of transport providers in (co)founding such ambiences, and makes a case for the importance of their prior manipulations. Taking the aircraft cabin as an example where transport operators labour to (pre)shape passenger experience, I interrogate the early organisational practices of one non‐Western airline – Singapore (SIA) – in deploying flight attendants known as Singapore Girls to imbue its cabins with certain strategic atmospheres by design. Empirical sections draw on staff newsletters and newspaper reports to show how SIA sought to induce comforting moods of Oriental hospitality, familiarity and quickened senses of care within its cabins through its crew members. While this research focuses on the design intentions of an airline, its findings have wide‐ranging implications on the future study of affective atmospheres in terms of their pre‐fabrication in a variety of consumer contexts. Relevant to scholars of geography, mobilities, tourism and beyond, this article draws ethical attention to the politics of such methods of anticipatory atmosphere‐making, and prompts further questions about their global circulation.